The procedure in the International Centre for Settlement of Investment Disputes - Babkina, Elena V.; Khomenko, Maria V. (Journal of the Belarusian State University. International Relations, 2018)
In the article the authors examine the procedure of arbitration and conciliation and applicable law at the International Centre for Settlement of Investment Disputes (“ICSID” or the “Centre”). Specifically, the authors compare arbitration and conciliation procedures and analyse the benefits and drawbacks of each as well as outline different positions taken by Tribunals in applying norms of international law to disputes at the Centre.